Mind-body practice as a primer to maintain psychological health among pregnant women–YOGESTA–a randomized controlled trial - Nadholta, Pooja; Kumar, Krishan; Saha, Pradip Kumar; Suri, Vanita; Singh, Amit; Anand, Akshay (Frontiers in Public Health, 2023)
Objective The objective of this study was to investigate the impact of Gestational Yoga-YOGESTA (Gestational Yoga), on the neuropsychology, quality of life, and personality of pregnant women. Design Open label, randomized controlled trial, used allocation concealment to allocate the treatment. Setting Department of Obstetrics and Gynecology and Neuroscience Research Lab, Department of Neurology, Post Graduate Institute of Medical Education and Research, Chandigarh, India. Participants We recruited a total of 100 pregnant women visiting the Outpatient Department of Obstetrics and Gynecology. Participants were aged between 18 and 35 with uncomplicated pregnancies and they were randomly assigned to either the Yoga group (YG) or the usual care group (UCG). A total of 77 pregnant women completed both the pre- and post-survey, with 34 participants in the Yoga group and 43 in the Usual care group. Intervention Pregnant women in their second and third trimesters were provided with a 16-week online Prenatal Yoga intervention. The intervention began after enrollment in the 2nd trimester, specifically between the 16th and 20th week, and was conducted 5 days a week until delivery, with an average intervention period of 47.18 ± 2.031 (mean ± SEM) days. Chief outcome measures We measured Perceived stress, Depression, Anxiety, Stress, and quality of life by using standard questionnaires. Results A total of 77 participants were included in the analysis, with 34 assigned to the Yoga group and 43 assigned to the control group. Most of the measured parameters demonstrated significant changes. The Yoga group exhibited a noteworthy decrease in perceived stress, depression, anxiety, and psychological stress, as well as an improvement in the psychological and environmental domains of QOL-BREF. Conversely, the control group demonstrated a significant increase in perceived stress, depression, anxiety, and psychological stress, along with a reduction in the physical, psychological, and social domains of QOL-BREF at the follow-up stage. Although the two groups were similar at baseline, the Yoga group showed substantial enhancements in perceived stress, depression, anxiety, physiological stress, and overall quality of life when compared to the control group at follow-up. Conclusion The study’s findings indicate that stress, anxiety, and depression are more likely to occur as gestational age progresses during pregnancy. Nevertheless, practicing Prenatal Yoga can effectively manage these changes and enhance the quality of life for expectant mothers. Clinical trial registration: Clinical Trials Registry-India, Identifier CTRI/2021/01/030827.